The effect of long-term COVID-19 infection on maternal and fetal complications: a retrospective cohort study conducted at a single center in China - Yao, Yang; Sun, Lanxu; Luo, Jing; Qi, Wenjin; Zuo, Xin; Yang, Zenglin (Scientific reports, 2024)
Investigate the effect of long-term COVID-19 on maternal and fetal complications. A retrospective cohort study was conducted. A total of 623 pregnant women who delivered in Kunming First People's Hospital from November 1, 2022 to July 31, 2023 were selected. By employing statistical methods, we compared the associations between maternal and fetal complications in pregnant women with acute COVID-19 during pregnancy, long-term COVID-19, and non-COVID-19 pregnant women. In the final 623 samples, there were 209 pregnant women with acute COVID-19, 72 pregnant women with long-term COVID-19, and 342 pregnant women without COVID-19. The epidemiological and clinical characteristics of all subjects were similar. Pregnant individuals who developed long-term COVID-19 during their pregnancy had an increased risk of experiencing gestational hypertension (OR 3.344, 95% CI 1.544–7.243), gestational diabetes mellitus (OR 2.301, 95% CI 1.290–4.102), and fetal intrauterine growth restriction (OR 2.817, 95% CI 1.385–5.952). Multivariate binary logistic regression analysis showed that this association remained consistent even after adjusting for confounders and performing subgroup analyses. Other maternal and fetal complications, such as premature rupture of membranes, preterm delivery, neonatal asphyxia, and transfer of neonates to NICU, did not exhibit statistically significant associations. After linear regression analysis, the platelet count (β: − 0.127, 95% CI − 0.001–0.000) of pregnant women with long-term COVID-19 was slightly lower than that of non-COVID-19 pregnant women, and the other coagulation parameters were not statistically significant. The incidence of gestational hypertension, gestational diabetes mellitus and fetal intrauterine growth restriction in pregnant women with long-term COVID-19 is significantly increased, but it does not further increase the coagulation status.